The Social environment of daily life and perceptions of police and/or court discrimination among African, Caribbean, and Black Youth - Peirone, Amy (Canadian journal of criminology and criminal justice, 2017)
Recent deaths of African-Americans at the hands of police and the creation of the protest movement Black Lives Matter has brought public attention to claims of racial profiling and police discrimination in the United States. In Canada, concerns about racial profiling centre on the disproportionate number of visible minority, particularly African-diasporic, individuals targeted in ''street checks'' or ''carding.'' This study used multivariate block logistic regression to compare the explanatory power of variables measuring different aspects of the social environment of daily life drawn from three theoretical frameworks (broken windows, routine activities, and critical race theory) when considering contact with police and perceptions of police and court discrimination in a sample of African-diasporic youth (N = 529) who self-identify as African, Caribbean, or Black in a mid-sized city in Ontario, Canada. All measures of the social environment contributed significantly to explaining contact and perceived discrimination. In addition, the significant increase in the variance explained for both contact and perceived discrimination with each successive block supports the conclusion that consideration of the social environment of daily life contributes to an understanding of youth-police contact and youth perceptions of police and courts. The study's findings add to the discussion of inequality and youth-police contacts and experiences, as well as to the Canadian criminological literature exploring relationships between police and racialized youth.